Plant homeodomain-leucine zipper I transcription factors exhibit different functional AHA motifs that selectively interact with TBP or/and TFIIB - Capella, Matias (2014)
Key message: Different members of the HD-Zip I family of transcription factors exhibit differential AHA-like activation motifs, able to interact with proteins of the basal transcriptional machinery. Homeodomain-leucine zipper proteins are transcription factors unique to plants, classified in four subfamilies. Subfamily I members have been mainly associated to abiotic stress responses. Several ones have been characterized using knockout or overexpressors plants, indicating that they take part in different signal transduction pathways even when their expression patterns are similar and they bind the same DNA sequence. A bioinformatic analysis has revealed the existence of conserved motifs outside the HD-Zip domain, including transactivation AHA motifs. Here, we demonstrate that these putative activation motifs are functional. Four members of the Arabidopsis family were chosen: AtHB1, AtHB7, AtHB12 and AtHB13. All of them exhibited activation activity in yeast and in plants but with different degrees. The protein segment necessary for such activation was different for these four transcription factors as well as the role of the tryptophans they present. When interaction with components of the basal transcription machinery was tested, AtHB1 was able to interact with TBP, AtHB12 interacted with TFIIB, AtHB7 interacted with both, TBP and TFIIB while AtHB13 showed weak interactions with any of them, in yeast two-hybrid as well as in pull-down assays. Transient transformation of Arabidopsis seedlings confirmed the activation capacity and specificity of these transcription factors and showed some differences with the results obtained in yeast. In conclusion, the differential activation functionality of these transcription factors adds an important level of functional divergence of these proteins, and together with their expression patterns, these differences could explain, at least in part, their functional divergence. © 2014 Springer-Verlag Berlin Heidelberg.